PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIF TIPE TGT MATERI PEMBAGIAN BERSUSUN DI KELAS IV SDN 24 PALEMBANG - Anisa Suryani; Amelia; Anggun Pratiwi; Anisa Suryani; Ade Irma; Diah Kartika Sari; Rika Puspita Sari; Bella Meliyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to describe the TGT model in order to improve student learning outcomes in class IV of SD Negeri 24 Palembang on graded division material. This research was conducted using a classroom action approach during July-August. The subjects in this research were all students in the IV.C class of SD Negeri 24 Palembang, totaling 39 students consisting of 18 male students and 21 female students. The research method used is classroom action research. Data was obtained through student test results at the pre-cycle, cycle I and cycle II stages. The results of the research show that there is an increase in learning outcomes in tiered division material using the TGT model. This is evident from the test scores obtained by students in class IV.C. The average score obtained by students in the pre-cycle was 63.5, then in cycle I the score rose to 71.5 and in cycle II the average score of students increased to 80.5. These results can be seen from cycle to cycle, there has been an increase in learning outcomes and has been able to encourage students to be more active, especially in learning in tiered division material using the TGT type cooperative learning model.